Supplies of bushmeat for livelihoods in logging towns in the Congo Basin - Tieguhong, J.C.; Zwolinski, J. (2009)
The focus of this study is on the importance of bushmeat to the economies of 99 hunting households in two logging towns, northern boundary of the Lobeke National Park, East Province of Cameroon. In this area, bushmeat was the major source of daily animal protein and an estimated 37 960 wild animals were killed each year or 104 animals per day. In general, 62% of the hunted animals were sold for cash income while 38% were consumed by the hunters and their families. An annual gross income from the bushmeat to hunters was estimated at 234 058 548 CFA Francs (US$ 469 117) while gross revenue from 11 other income generating activities accessed by the hunters was only 4.5% of the income from hunting. Various costs represented 69.4% of the gross hunting revenues. Average hunting income was twice higher than the income of a junior technician and about the same as that of a senior technician working at SEFAC (logging company). The income of hunters at the higher end of the income range was comparable to those of mid-career SEFAC managers. Such a lucrative business provides economic incentives to hunting despite all the suppressive measures. Moreover, the importance of a large bushmeat market is rarely detected and seriously taken into account when designing conservation policies aimed at protecting wildlife and fighting against poaching. The study stresses the need for empathetic approaches that favour more deliberate development and conservation policies while dealing with bushmeat issues in logging towns of the region.